Use of Information and Communication Technology (ICT) and E-Governance in Dhangadhi Sub-Metropolitan City, Nepal - Sharma, Bed Prakash (NPRC Journal of Multidisciplinary Research, 2025)
Background: The Government of Nepal has recognized Information and Communication Technology (ICT) as a transformative tool for promoting development, improving public service delivery, and fostering good governance. The 2015 National ICT Policy outlines key priorities for leveraging technology across sectors. E-governance, in particular, is envisaged as an enabler of efficient, transparent, and citizen-centered governance, with local municipalities serving as critical platforms for its implementation. However, the journey from policy to practice is often challenged by infrastructural, institutional, and human capacity constraints.Objectives: This study aims to investigate the role of e-governance in promoting transparency, accountability, and corruption reduction in local governance. Specifically, it explores the use of ICT in e-governance within the context of Dhangadhi Sub-Metropolitan City, an established municipality in Nepal.Methods: The research adopted a positivist paradigm and a descriptive research design. Data were collected through structured questionnaires and interviews with 130 municipal staff members of Dhangadhi Sub-Metropolitan City, selected via simple random sampling. Secondary data were obtained from government publications, policy documents, and relevant literature. Quantitative data were analyzed to assess the status of ICT infrastructure, software application, and digital service delivery.Findings: The findings reveal a mixed implementation status. While foundational ICT infrastructure, such as computer availability and maintenance, is reasonably established (mean scores 3.2-3.6), key digital governance features are underdeveloped. Core administrative software for accounting, tax collection, and e-procurement is widely used and well-regarded (mean scores up to 4.2). However, systems for citizen interaction, grievance handling, social mobilization, and office automation are largely absent or poorly implemented (mean scores 1.2-2.7). Municipalities have official websites and emails, but lack advanced features like content management systems and interactive service portals. Social media is primarily used for one-way information dissemination, not for participatory engagement.Conclusion: The study concludes that while Nepal has made significant strides in establishing the technological foundations for e-governance at the local level, its implementation remains partial and fragmented. The gap between technological availability and effective utilization highlights significant socio-technical barriers, including bureaucratic resistance, limited digital literacy among staff, and a lack of citizen-centric service design. For e-governance to fulfill its potential in enhancing transparency and accountability, a shift from a technology-driven to a people-centered approach is necessary.Implications: The findings imply that future e-governance strategies in Nepal must move beyond infrastructure provision to address deeper institutional and human capacity challenges. Policy should focus on:• Institutional Reform: Incentivizing digital innovation within the bureaucracy and fostering a culture of accountability and transparency.• Capacity Building: Implementing continuous and widespread digital literacy and technical training programs for civil servants.• Citizen-Centric Design: Developing interoperable systems that prioritize citizen needs, such as integrated grievance redressal mechanisms, interactive service portals, and open data initiatives.Scalable Models: Replicating successful participatory models, like those initiated by the Rural Urban Partnership Programme (RUPP), which combine technology with community mobilization.